PENGARUH PENGGANTIAN REED VALVE SUZUKI SATRIA 120 R TERHADAP TORSI DAN DAYA - , KURNIA, Ir, Harjono, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Reed valve is a very important component in the machine 2 steps . Reed valve serves to prevent the gas back into the carburetor when the pressure of the gas piston . Reed valve is part of the engine fuel system 2 steps . This study was conducted to determine the effect of Reed valve replacement on power ( power ) and torque ( torque ) . standard reed valve Suzuki Satria 120 R is replaced with a reed valve and reed valve local racing , then tested to determine the power ( power ) and torque ( torque ) engine produced . So as to compare the results obtained between standard reed valve , racing and regular. The testing process is done by measuring the power and torque generated each reed valve . Engine power and torque were measured by using a dyno test with Dynamometer type SD 325 . after testing , the data generated in the form of graphs as well as the amount of power in units of horsepower ( hp ) and torque with units ( Nm ) . The power generated is a standard reed valve 19.5hp at 10195rpm and torque of 3.64 Nm at 10082 rpm . Peak power generated local reed valve and reed valve racing ( Sharke ) - located at a higher rpm than the standard reed valve , respectively 10324 rpm and 10211 rpm . Torque produced local reed valve and reed valve racing ( Sharke ) respectively increased 0.10 Nm and 1.21 Nm.